Deferred Enrollment: Chicano/Latino Males, Social Mobility and Military Enlistment. Issue 1 (January 2020) - Martinez, Eligio; Huerta, Adrian H.
Chicanos/Latinos comprise the largest racial and ethnic population in the U.S. public K-12 schools, yet hold some of the largest rates of academic underperformance in high school and college completion. This study aims at understanding the academic trajectories of five Chicano/Latino males and their decision to enlist in the military after high school graduation. Using in-depth semistructured interviews, participants discussed the role that high school structures, family, social capital, and sociocultural forces played in their career decision-making process. Results showed that students viewed the military as a way of upward social mobility and their most viable career option after completing high school. The study also highlights the lack of resources available to students who may not be viewed as college material by school personnel.